Industrial applicability of enzymatic and whole-cell processes for the utilization of C1 building blocks - Giovanni Davide Barone; Ina Somvilla; Hannah Pia Franziska Meier; Anna Christina R. Ngo; Thomas Bayer; Fabio Parmeggiani; Viktoria Rehbein; Johann A. Hlina; Pablo Domínguez de María; Uwe T. Bornscheuer; Dirk Tischler; Sandy Schmidt (Nature Communications)
Abstract Chemicals produced through enzymatic reactions play a key role in the transition from a linear petrol-dependent to a circular bioeconomy. One promising approach is the conversion of single carbon (C1) molecules by biocatalysts to value-added products. Although progress has been made, current biological methods remain less cost-competitive than established chemical processes. Here, we review how single and multi-enzyme transformations, natural C1-trophic microorganisms, and organisms with transplanted synthetic C1 assimilation pathways can synergize to strengthen the competitiveness of C1-based biomanufacturing. To explore the current state-of-the-art and assess the potential of C1 biomanufacturing, we highlight the aforementioned bio-based methodologies and evaluate their industrial applicability through an overview of granted patents.